Persepsi Masyarakat Tentang Pentingnya Menjaga Imunitas Tubuh Pada Masa Darurat Bencana COVID-19 - Ika Rahmawati; Putri Kristyaningsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Covid-19 disease or Corona viruses disease 19 is a transmitted disease that caused by corona viruses. Corona viruse is a virus that can attck both of humans and animals. Covid -19 caused health disturbance even death on humans. Died persons of Covid-19, most of them are found have comorbid disease or they are elderly. People with chronic disease (ex.: Diabetic, heart disesase, cancer, hypertension) or elderly, have a lower immunity than those that younger or in good health condition. Covid 19 is non-natural disaster and has had become a pandemic in all over the world. An effort that we can use to fight Covid 19 is increasing the body immunity, since the good immunity can heal viral disease. By increasing the body immunity, it can prevents and heals the body from Covid 19. People awareness of the importance of immunity must be elevated. The purpose of this research is to knowing how is people’s perception about body immunity during this covid 19 emergency disaster. This research using observational analytic design with purposive sampling technique, the sum of the respondents are 50. It uses google form for the research instrument. The result shows that people’s perception about body immunity during covid 19 emergency disaster are mostly good. People already understand that immunity is very important to improve during the Covid-19 pandemic <w:LsdException Locked=